Influence of rain and wind dynamics on lodging of rice (Oryza sativa) varieties under rainfed agro-ecology - ADIKANT PRADHAN; A DIXIT; A SONKAR; L TALUKDAR (The Indian Journal of Agricultural Sciences)
The present study was carried during rainy (kharif) seasons of 2021 and 2022 at Research Farm of S G College of Agriculture and Research Station (Indira Gandhi Krishi Vishwavidyalaya, Raipur, Chhattisgarh), Jagdalpur, Chhattisgarh to find the characters responsible for lodging of rice (Oryza sativa L.) under natural condition considering weather parameters. A total of 50 varieties of rice were sown in 5.0 m × 5.0 m plots maintaining strip distance of 10 m for providing proper air movement. However, the lodging tolerance of rice varieties was obviously different from each other and 7 key factors that highly influenced the lodging were studied. Rice varieties were sown as horizontal to the length of plot and just orthogonal to width. The strip was uniformly divided in 50 plots with 0.5 m inter-plot distance and 10 m apart to strips. The recommended doses of 80:60:40 kg of NPK/ha were given through straight fertilizers. The mean annual rainfall was received 1408 mm during June–September. In September, slight shifting of wind was recorded with an average speed of 4.49 km/h in north-east and north-west direction in evening and morning hours, respectively which really impacted on basal nodes. September onwards gradually declined in wind speed from 4.40 to 3.15 km/h was recorded. Correlation study was synchronized both the factors, wind and rain together made susceptibility to lodging the varieties like Benisar, Bewara,Chhota Kabari, Chhota Kabari 1, Dagad desi 2, Kakai 1, Kankeri 1, Kanji 1, Kanji, Kantabuta, Kardhana, Karahani, Kari, Karikhuji, Kohikari and Koliya. The variety (Barhi, Benisar, Kalasu and Kanji 1) attained more than 140 cm height coupled with >6 leaves per plant (Chanda and Kanji 1) had higher lodging. Lodging was also observed in leaf length >70 cm that produced more biomass in Bhaya gonad, Butabari and Kankeri 1. Plant height showed the highest eigen value and reverse was in stem thickness; whereas number and length of leaf were almost similar and expressed greater affinity than leaf width and 1st nodal distance in lodging.